'Thoughts on authoring the past as history'. Issue 4 (1st October 2016) - Munslow, Alun
Abstract: This article examines the process of creating a history from the historian's initial epistemic genre decision, then to their constitution of the paratextual nature of the history as it is authored in terms of the creation of the historian's 'story space', 'discourse' and 'narration'. This requires evaluating the authorial decisions of the historian as they deploy the key concepts of focalization, agent intentionality, and 'change over time'.